Environmental Liability in Civil Law Systems (Revista da Faculdade de Direito, Universidade de São Paulo, 2012)
The Topos „Liability“ guides the present society. Its use does not normally bring opposition in the legal debate. To stablish the concept of Liability, the State stablishes rules and institutions, to divide the activities between State and society.